-CPA دور البنوك التجارية كأداة في ترقية الصادرات من خلال آليات التمويل قصيرة الأجل-دراسة حالة في بنك - دهوب عبد المجيد; محيفر صهيب; عبد الحفيظي إبراهيم (جامعة عمار ثليجي الاغواط, 2022)
The banks are considered as the fundamental spine of the national economy for their contribution in the local and national developments as they finance the economic institutions .activities and all other economic agents in general. May be the main activities in which the banks importance is visible .is the foreign economy regarding the financing and contributing for their promotion and along side with the big changes the world has known in field of international commercial exchanges and the expansion of economic relations among different states of the world .many financing problem have appeared hens contributing to constitute a barrier before prosperity and growth of these exchange and the topic of foreign economy has a great importance we have at temted in our study to shed a light on the role of commercial banks with in the foreign commerce concerning their services to foreign commerce and knowing the adopted financing ways and the esctent of meeting the dealers needs in addition to algerian policy for promoting this sector.